The influence of graphite filler on the viscoelastic and mechanical characteristics of PC/ABS hybrid composite for automotive applications / Basanta Kumar Behera ... [et al.] - Behera, Basanta Kumar; Parveen J, Shahitha; Manohar, Murali; Begum, Shamshath; Thirumurugan M, Thirumurugan M (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
This work aims to enhance the viscoelastic and mechanical properties of the neat Polycarbonate/Acrylonitrile Butadiene Styrene (PC/ABS) blend by incorporating graphite filler. Thermoplastic composites were prepared with PC/ABS as the matrix and graphite powder as fillers of 3, 6, and 9 wt% by injection molding. The influence of graphite particulate on the mechanical properties of PC/ABS/graphite composite was studied through tensile strength, tensile modulus, percentage elongation, impact strength, flexural strength, and modulus. The results show a 20% improvement in the tensile and flexural modulus of the PC/ABS/graphite composite compared to the neat PC/ABS blend. However, the tensile strength and percentage elongation were reduced by 11.64% and 29.63%, respectively. The storage modulus with 9 wt% of graphite in the PC/ABS blend has the highest modulus over the entire temperature range compared to the neat PC/ABS blend. The addition of graphite filler to the PC/ABS blend increased the tensile, flexural, and storage modulus, even though some mechanical attributes were compromised. The viscoelastic, mechanical, and thermal properties were enhanced by adding graphite as a filler to help plastic product designers design plastic products for automobile applications.